Analysis of Factors Affecting the Purchasing Power of Indonesian Societies in the 2013-2023 Period - Alexandra, Joy; Fitanto, Bahtiar (Journal of Development Economic and Social Studies, 2026)
Purchasing power refers to an individual's ability to consume goods or services. There is a considerable amount of evidence indicating a weakening of the purchasing power of the Indonesian people in 2024. This research aims to analyse the factors that influence the purchasing power of the Indonesian population from 2013 to 2023. This study focuses on five variables: inflation, interest rate, value-added tax (VAT), consumer credit, and the open unemployment rate. The analytical method used in this research is multiple linear regression analysis. The results of this research are that inflation and credit consumption have a significant and positive effect. Open unemployment rate has a significant negative effect on purchasing power. Interest rates and VAT do not significantly affect purchasing power.